Treatment and care of women with epilepsy before, during, and after pregnancy: a practical guide - Bruna Nucera; Francesco Brigo; Eugen Trinka; Gudrun Kalss (Therapeutic Advances in Neurological Disorders, 2022)
Women with epilepsy (WWE) wishing for a child represent a highly relevant subgroup of epilepsy patients. The treating epileptologist needs to delineate the epilepsy syndrome and choose the appropriate anti-seizure medication (ASM) considering the main goal of seizure freedom, teratogenic risks, changes in drug metabolism during pregnancy and postpartum, demanding for up-titration during and down-titration after pregnancy. Folic acid or vitamin K supplements and breastfeeding are also discussed in this review. Lamotrigine and levetiracetam have the lowest teratogenic potential. Data on teratogenic risks are also favorable for oxcarbazepine, whereas topiramate tends to have an unfavorable profile. Valproate needs special emphasis. It is most effective in generalized seizures but should be avoided whenever possible due to its teratogenic effects and the negative impact on neuropsychological development of in utero- exposed children. Valproate still has its justification in patients not achieving seizure freedom with other ASMs or if a woman decides to or cannot become pregnant for any reason. When valproate is the most appropriate treatment option, the patient and caregiver must be fully informed of the risks associated with its use during pregnancies. Folate supplementation is recommended to reduce the risk of major congenital malformations. However, there is insufficient information to address the optimal dose and it is unclear whether higher doses offer greater protection. There is currently no general recommendation for a peripartum vitamin K prophylaxis. During pregnancy most ASMs (e.g. lamotrigine, oxcarbazepine, and levetiracetam) need to be increased to compensate for the decline in serum levels; exceptions are valproate and carbamazepine. Postpartum, baseline levels are reached relatively fast, and down-titration is performed empirically. Many ASMs in monotherapy are (moderately) safe for breastfeeding and women should be encouraged to do so. This review provides a practically oriented overview of the complex management of WWE before, during, and after pregnancy.